“Participación y activismo político en redes sociales por parte de los jóvenes universitarios de la UTC en la precampaña electoral del período 2019-2022” - Clavijo Pinza, Josselyn Cristina (2020)
The problem about the participation and political activism in social networks by young of the Technical University of Cotopaxi with regard to the 2019-2022 electoral campaign, aims to analyze the use of social networks in political issues like pre electoral processes, because there is a certain political apathy for the youth population about this. In this way, the main goal of this project was to know the ways and degrees of participation and political activism on Facebook and Twitter by young people between 18 and 29 years of age who defray in Latacunga canton. The methodological strategy has a mixed focusing due to its level of descriptive research using the survey technique, since the implemented analysis needs support, the application of interview and documentary analysis was also used in the use of analytical digital platforms about electoral process. Among the main results, it was identified that the social network most used to know electoral political information is Facebook, in addition to knowing how young people participate and perform their political activism, in this social network we found a way to provide Likes or reactions in aspects of electoral policy in a good and regular range. Therefore, it was possible to verify the influence of social networks for the election of a candidate. This research project contributes significantly in aspects related to politics and society, since knowing their political performance was able to identify, what is the interest that young people have in delivering power to a president. Among the main conclusions established that there is little political participation in these social networks by the younger in electoral themes and affirm at a medium level their political activism.